2024
DOI: 10.3389/fphar.2024.1330374
|View full text |Cite
|
Sign up to set email alerts
|

Novel in vitro evidence on the beneficial effect of quercetin treatment in vascular calcification

E. Ceccherini,
I. Gisone,
E. Persiani
et al.

Abstract: Vascular calcification is a pathological chronic condition characterized by calcium crystal deposition in the vessel wall and is a recurring event in atherosclerosis, chronic kidney disease, and diabetes. The lack of effective therapeutic treatments opened the research to natural products, which have shown promising potential in inhibiting the pathological process in different experimental models. This study investigated the anti-calcifying effects of Quercetin and Berberine extracts on vascular smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Presently, the predominant constituents under investigation in wolfberry are polysaccharides and flavonoids, with quercetin being a predominant flavonoid constituent. Studies have indicated that quercetin can mitigate vascular calcification and reduce inflammatory responses ( Ceccherini et al, 2024 ). Furthermore, quercetin has been observed to alleviate liver injury resulting from cholestasis, stress, inflammation, and fibrosis ( Abushady et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the predominant constituents under investigation in wolfberry are polysaccharides and flavonoids, with quercetin being a predominant flavonoid constituent. Studies have indicated that quercetin can mitigate vascular calcification and reduce inflammatory responses ( Ceccherini et al, 2024 ). Furthermore, quercetin has been observed to alleviate liver injury resulting from cholestasis, stress, inflammation, and fibrosis ( Abushady et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%